2002
DOI: 10.3184/030823402103172554
|View full text |Cite
|
Sign up to set email alerts
|

Protonation mechanisms of Nickel Complexes Relevant to Industrial and Biological Catalysis

Abstract: The sites of protonation and the subsequent rearrangement reactions of simple nickel complexes containing hydride, thiolate and alkyl ligands are reviewed, and the relevance of these reactions to the action of certain nickelbased catalysts are discussed. Summary Protonation at the metal and ligand is central to the understanding of how both enzymes and industrial catalysts operate at the molecular level. The recurring theme in studies on the protonation of all metal complexes is that the ultimate residence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In some postulated PT mechanisms, a cysteine terminally bound to the nickel ion of the active site (Scheme ) accepts a proton during catalysis as supported by experimental , and theoretical studies, and by organometallic model systems. The hypothesis is also circumstantially supported by the natural occurrence of [NiFeSe] H 2 ases, which contain a terminal selenocysteine in place of a cysteine and exhibit higher overall activity, lower product inhibition, and enhanced O 2 tolerance. Multiple PT pathways connecting a protonated cysteine thiol to the protein surface have been hypothesized based on X-ray crystallography, ,,, site directed mutagenesis in conjunction with spectroscopic and kinetic methods, , and theoretical simulations. ,, Such studies support a pathway immediately beyond the first coordination sphere of the nickel ion involving a conserved glutamate adjacent to a terminal cysteine (E–C mechanism in Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…In some postulated PT mechanisms, a cysteine terminally bound to the nickel ion of the active site (Scheme ) accepts a proton during catalysis as supported by experimental , and theoretical studies, and by organometallic model systems. The hypothesis is also circumstantially supported by the natural occurrence of [NiFeSe] H 2 ases, which contain a terminal selenocysteine in place of a cysteine and exhibit higher overall activity, lower product inhibition, and enhanced O 2 tolerance. Multiple PT pathways connecting a protonated cysteine thiol to the protein surface have been hypothesized based on X-ray crystallography, ,,, site directed mutagenesis in conjunction with spectroscopic and kinetic methods, , and theoretical simulations. ,, Such studies support a pathway immediately beyond the first coordination sphere of the nickel ion involving a conserved glutamate adjacent to a terminal cysteine (E–C mechanism in Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the factors which control the rates and mechanisms of protonation of metal complexes is fundamental in defining the elementary reactions both of certain metalloenzymes, including nitrogenases and hydrogenases, , and of certain industrially and economically important catalysts, such as those involved in the isomerization or hydrocyanation of alkenes and alkynes. , Previous kinetic studies have revealed that apparently simple protonation reactions of transition metal complexes can be mechanistically complicated, because protonation can occur at more than one site in these complexes: either metal or ligand. , In many complexes rapid protonation at one site (kinetically favored protonation site) is followed by intra- or intermolecular rearrangements in which the proton “moves” to another site (thermodynamically favored protonation site) to give the product. Much of this chemistry has been defined with complexes containing metal−carbon bonds, where the rates of protonation of both the metal and carbon sites are appreciably slower than the diffusion-controlled limit ( k diff = 1 × 10 10 dm 3 mol -1 s -1 ) .…”
Section: Introductionmentioning
confidence: 99%